Cory magic : her peoples' stories - Marian Pastor Roces ; Monina Allarey Mercado;Raul Rodrigo (Quezon City, Philippines : ABS-CBN Publishing, 2009)
This book is ABS-CBN's tribute to Corazon C. Aquino. We believe that telling her story well, in words and images, helps to spread her values among our people and helps give meaning to the work we do.
1. Her People's farewell 2. Raphael "Rapa" Lopa 3. Manuel "Manoling" Francisco, SJ 4. Bishop Socrates "Soc" Villegas 5. Photo Folio 6. Her Struggle 7. Teodoro "Teddy Boy" Locsin Jr. 8. Alfredo 'Alran" Bengzon Md. 9. Renato "Rene" de villa 10. Photo Folio 11. Her fight for freedom 12. Ma. Elena "Ballsy" Aquino Cruz 13. Manuel " Mar" Araneta Roxas II 14. Photo Folio
Keywords: AQUINO, CORAZON COJUANGCO